EPIDEMIOLOGICAL SURVEY OF BANCROFTIAN FILARIASIS IN TANGEDU (GUNTUR, AP) - V.VIVEKA VARDHANI; R. ADINARAYANA (The Bioscan, 2011)
Filariasis is major public health illness in Tangedu (Guntur District) (Andhra Pradesh) (India) and 30-32% of the population is estimated to be at high risk. Inspite of repeated attempts to control filariasis, the disease transmission is perennial and persistent mostly transmitted by Culex quuinquefasciatus. The transmission of lymphatic filariasis is correlated with Mf rate, disease rate, infection rate and infectivity rate and found that the disease transmission is very high in Tangedu.